The identity of Acanthosoma vicinum, with proposal of a new genus and species level synonymy (Hemiptera: Heteroptera: Acanthosomatidae) - Tsai, Jing-Fu; Rédei, Dávid (Zootaxa, 2015)
The identity of Acanthosoma vicinum Uhler, 1861 (type species of the monotypic genus Grossaria Kumar, 1974) is clarified based on reexamination of the lectotype. The following new combination and new subjective synonymies are proposed: Elasmucha Stål, 1864 = Grossaria Kumar, 1974, syn. nov.; Elasmucha vicina (Uhler, 1861), comb. nov. (transferred from Acanthosoma) = Elasmucha dorsalis (Jakovlev, 1876), syn. nov. Reversion to the senior name E. vicina is considered to be undesirable, therefore, in order to preserve stability, no nomenclatural changes are proposed in this paper, but an application has simultaneously been submitted to the International Commission on Zoological Nomenclature to give the specific name dorsalis precedence over the specific name vicinum.